EFFECT OF RETURN ON ASSETS (ROA), EARNINGS PER SHARE (EPS), AND PRICE EARNING RATIO (PER) ON SHARE PRICES OF COMPANIES IN THE PROPERTY AND REAL ESTATE SECTOR LISTED ON THE IDX 2021-2022 - Ariawan Ariawan; Tri Endar Susianto; Eko Cahyo Mayndarto (Jurnal Ekonomi, 2023)
Indonesia's economic growth is increasing year after year. Property and real estate sector companies are one of the nation's economic growth pillars. Property and real estate companies are industrial firms that provide services by facilitating the development of dynamic areas. The purpose of this research is to look at the impact of Return on Assets (ROA), Earnings Per Share (EPS), and Price Earning Ratio (PER) on stock prices in the property and real estate sector listed on the IDX from 2021 to 2022. This study used data from the quarterly financial reports of five companies in the property and real estate sector, namely SMRA, DILD, BSDE, JRPT, and MTLA, obtained from the IDX. The analysis technique used is the classical assumption test, which includes the normality, multicollinearity, and heteroscedasticity tests, as well as panel data regression and the coefficient of determination test. This research was tested using the EViews10 application. The partial test results show that the ROA and PER variables have no effect on stock prices. While the variable EPS influences stock prices. While the results of the simultaneous testing of the ROA, EPS and PER variables simultaneously affect the stock price variable.